ORGANIC FARMING APPROACH FOR SUSTAINING PRODUCTIVITY OF RAINFED GROUNDNUT - SOLANKI, R.M.; BHALU, V.B.; JADAV, K.V. (Annals of Agricultural Research, 2014)
A field experiment on fixed site was conducted during the khaif seasons of 1999, 2000 and 2001 to study the response of organic manures on yield attributes of rainfed groundut and soil nutrient status. Application of FYM @ 10 t/ha recorded significantly higher pod yield (2785 kg/ha) and gross return of Rs. 314471 / ha with THE maximum net realization of Rs. 17597 / ha in pooled results followed by application of RDF. FYM applied @ 10 t/ha every year on a same site resulted in significant increase in available N, P2O5 and K2O.